Photopharmacological control of cell signaling with photoswitchable lipids. (April 2022) - Mukhopadhyay, Tufan K.; Morstein, Johannes; Trauner, Dirk
Abstract: Many aspects of cell signaling are controlled by lipids. Several signaling lipids have been functionalized with an azobenzene photoswitch to control underlying signaling dynamics with light. Herein, we provide an overview of signaling photolipids developed to date focusing on their biological applications. These include immunomodulation, kinase translocation, apoptosis, ion channel activation, G-protein coupled receptor activation, and neurogenesis.